Strategi Pengembangan Sektor Ekonomi Kreatif - Nuriansyah, Fazar; Prabowo, Rakhmat; Setiawan, Agung; Geminastiti Hilmiatussadiah, Kinanti; Nurul Fadhillah, Saskia (Jurnal Pendidikan Ekonomi, 2026)
The creative economy is one of the drivers of economic growth in Indonesia, contributing significantly to GDP and job creation, particularly through MSMEs. Despite its great potential, this sector faces obstacles in the form of limited human resources, market access, capital, and the digitalization gap. This study aims to identify strategies for developing the creative economy in Indonesia. The method used is qualitative, based on a Systematic Literature Review (SLR) with the PRISMA protocol. Of the 243 articles identified, 20 articles met the inclusion criteria and were analyzed thematically. The results of the study show that the development of the creative economy requires a multidimensional strategy. The main strategies identified include strengthening human resource capacity, product innovation, digital promotion and marketing, developing supporting infrastructure, and triple helix and penta helix collaboration. The application of the Strength–Opportunity strategy proved to be effective in utilizing internal potential to capture external opportunities. In addition, the cluster model in certain sub-sectors, such as culinary, crafts, and fashion, encouraged increased competitiveness and regional identity. These findings confirm that the integration of these strategies can strengthen the creative ecosystem, enhance local competitiveness, and promote sustainable economic growth. This research contributes by providing a strategic framework that can be used as a reference for policymakers and practitioners in developing the creative economy in Indonesia.